Phosphor particles, composites and light-emitting devices

By designing tiny recesses on the surface of fluoride fluorescent particles and adopting specific manufacturing methods, the problem of insufficient luminous characteristics in the existing fluoride fluorescent particles in white LED applications is solved, and the effect of higher brightness and excellent color reproducibility is achieved.

CN116917438BActive Publication Date: 2025-02-28DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280017931.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2022-03-18
Publication Date
2025-02-28
Estimated Expiration
2042-03-18

AI Technical Summary

Technical Problem

In the application of existing fluoride phosphors, the luminescence characteristics have not been optimized, especially in terms of brightness and color reproducibility.

Method used

By designing that the surface of the fluorescent particles has a tiny recess and adopting specific manufacturing methods and conditions, such as cooling in a hydrofluoric acid solution and pouring into an appropriate raw material, a fluoride phosphor with excellent luminescence characteristics is formed.

Benefits of technology

Higher brightness and excellent color reproducibility are achieved, and the luminous performance of fluoride phosphors in white LEDs is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116917438B_ABST
    Figure CN116917438B_ABST
Patent Text Reader

Abstract

A phosphor particle, whose composition is represented by the general formula (1): A2MF6:Mn, has at least one micro-concave portion on the surface. In the general formula (1), the element A is one or more alkali metal elements including K, and the element M is a simple substance of Si, a simple substance of Ge, or a combination of Si and one or more elements selected from Ge, Sn, Ti, Zr and Hf.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to phosphor particles, composites and light-emitting devices. Background Art

[0002] As a phosphor that can convert blue light emitted by a blue light-emitting diode into red light, a fluoride phosphor represented by K2SiF6:Mn (often abbreviated as "KSF phosphor" or the like) is known. This phosphor is efficiently excited by blue light. In addition, the half-peak width of the emission spectrum of this phosphor is narrow and sharp. Therefore, by using this phosphor as a red phosphor, a white LED with high brightness and excellent color rendering and color reproducibility can be realized.

[0003] As a prior art of fluoride phosphors, for example, Patent Document 1 can be cited. Patent Document 1 describes a fluoride phosphor having a composition of the general formula A2M (1-n) F6:Mn 4+ n Indicates that the bulk density is 0.80g / cM 3 In the general formula, 0<n≤0.1, element A is one or more alkali metal elements including K, and element M is Si single substance, Ge single substance, or a combination of Si and one or more elements selected from Ge, Sn, Ti, Zr and Hf.

[0004] In addition, as a prior art of fluoride phosphors, Patent Document 2 can also be cited. Patent Document 2 describes a phosphor characterized in that a part of a mother crystal represented by A2BF6 (wherein A is K, Na, Rb or Cs, and B is Si, Ge, Sn, Ti or Zr, and does not include a combination of K and Si, K and Ge, and K and Ti) is replaced with a crystal structure composed of a transition metal as an activator.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-001897

[0008] Patent Document 2: International Publication No. 2009 / 119486 Summary of the invention

[0009] As white LEDs become more common, there is a demand for further improvement in the light emission characteristics of fluoride phosphors.

[0010] The present inventors have conducted various studies with the aim of obtaining a fluoride phosphor having excellent light-emitting properties.

[0011] The present inventors have completed the invention provided below and solved the above-mentioned problems.

[0012] According to the present invention, the following phosphor particles are provided.

[0013] A phosphor particle having a composition represented by the following general formula (1) and having at least one micro-concave portion on the surface.

[0014] General formula (1): A2MF6:Mn

[0015] In the general formula (1),

[0016] Element A is one or more alkali metal elements including K,

[0017] The element M is Si as a single substance, Ge as a single substance, or a combination of Si and one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf.

[0018] Furthermore, according to the present invention, there is provided a composite body comprising: the above-mentioned phosphor powder; and a sealing material for sealing the phosphor powder.

[0019] In addition, according to the present invention, there is provided a light-emitting device comprising: a light-emitting element that emits excitation light, and the above-mentioned complex that converts the wavelength of the excitation light.

[0020] According to the present invention, a fluoride phosphor having excellent light-emitting properties is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a diagram for explaining the form of micro recessed portions.

[0022] Figure 2 is a diagram showing an example of a light emitting device.

[0023] Figure 3 This is an electron microscope image of the phosphor particles produced in Example 1.

[0024] Figure 4 This is an electron microscope image of the phosphor particles produced in Example 2.

[0025] Figure 5 This is an electron microscope image of the phosphor particles produced in Comparative Example 1. DETAILED DESCRIPTION

[0026] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. All drawings are for illustration purposes only. The shapes, dimensional ratios, etc. of the components in the drawings do not necessarily correspond to actual products.

[0027] <Phosphor particles>

[0028] The composition of the phosphor particles of the present embodiment is represented by the following general formula (1): With this composition, the phosphor particles of the present embodiment usually convert blue light emitted from a blue LED into red light.

[0029] General formula (1): A2MF6:Mn

[0030] In the general formula (1),

[0031] Element A is one or more alkali metal elements including K,

[0032] The element M is Si as a single substance, Ge as a single substance, or a combination of Si and one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf.

[0033] In addition, from the viewpoint of “shape”, the phosphor particles of the present embodiment have at least one micro-concave portion on the surface.

[0034] When the phosphor particles of this embodiment are irradiated with blue light, it is estimated that the blue light “enters” the micro-concave portions and is converted into red light without loss, so that the light emission characteristics are estimated to be improved.

[0035] The phosphor particles of the present embodiment can be manufactured by using appropriate raw materials and adopting appropriate manufacturing methods and manufacturing conditions. The details of the manufacturing method will be described later. The phosphor particles of the present embodiment can be obtained by precipitating the phosphor particles in water and appropriately selecting and controlling the order in which various raw materials are put into water, the temperature when the raw materials are put into water, etc.

[0036] The description of the phosphor particles of this embodiment will be continued.

[0037] (Morphology of micro-concave portions)

[0038] Examples of specific shapes of micro-recesses are shown in the microscope images shown in the examples described later, but are not shown for the sake of explanation. Figure 1 Schematic representations of micro-depressions and their vicinities are shown in FIG.

[0039] Figure 1 In the embodiment, the micro-concave portion exists on the substantially planar surface of the phosphor particle. The micro-concave portion may be located on the substantially planar portion of the phosphor particle surface or on the non-planar portion of the phosphor particle surface.

[0040] Figure 1 In the embodiment, the micro-recesses become smaller as they go deeper, but the micro-recesses are not limited to such a form. For example, the micro-recesses may have a substantially constant diameter in the depth direction like a well.

[0041] The depth of the micro-concave portion, that is, the distance between the surface of the phosphor particle and the bottom of the micro-concave portion, is preferably 0.5 μm to 20 μm, and more preferably 1 μm to 10 μm.

[0042] The shape of the opening of the micro-recess, i.e., the "edge" of the micro-recess on the surface of the phosphor particle is not particularly limited, and is preferably a triangular shape. The "triangular shape" here may not be a mathematically strict triangular shape, as long as it is a shape that can be recognized as a triangle in common sense. For example, a part or all of the three sides of the triangle may not be a strict straight line.

[0043] The triangle may be an equilateral triangle, an isosceles triangle, or a triangle whose three sides are all of different lengths.

[0044] The maximum diameter of the opening of the micro-recess is preferably 0.5 μm to 20 μm, more preferably 1 μm to 10 μm. The maximum diameter is obtained by measuring the maximum diameter of the opening present in a two-dimensional image of the phosphor particles taken with an electron microscope.

[0045] The maximum diameter of the opening in the two-dimensional image of the phosphor particles taken with an electron microscope varies depending on the direction of the phosphor particles taken. However, in view of this deviation, if the maximum diameter falls within the above numerical range, better luminescence characteristics can be obtained. In other words, the above numerical range of 1μm to 20μm is a numerical range obtained by taking into account the deviation of the maximum diameter depending on the direction of the phosphor particles taken.

[0046] (Particle Agglomeration)

[0047] The phosphor particles of the present embodiment may be primary particles or secondary particles formed by aggregation of primary particles. In other words, the phosphor particles of the present embodiment may have micro-concave portions on the surface of the secondary particles.

[0048] Generally, if phosphor particles are secondary particles, the light emission characteristics tend to be reduced. However, the phosphor particles of this embodiment may suppress the reduction of light emission characteristics by having micro-concave portions.

[0049] (The size of the particle itself)

[0050] The major axis obtained from an electron microscope image of the phosphor particles of this embodiment is preferably 3 μm to 150 μm, more preferably 5 μm to 100 μm, and even more preferably 10 μm to 50 μm. When the major axis is an appropriate size, better light emission characteristics can be obtained.

[0051] The image obtained by photographing phosphor particles with an electron microscope is a two-dimensional image, and the long axis has a deviation depending on the direction of the phosphor particles photographed. However, in view of this deviation, if the long axis falls within the above numerical range, better luminescence characteristics can be obtained. In other words, the above numerical range of 3μm to 150μm is a numerical range obtained by taking into account the deviation of the long axis depending on the direction of the phosphor particles photographed.

[0052] (Composition: general formula (1))

[0053] Element A is one or more alkali metal elements including K. Specifically, it may be a simple substance of K, or a combination of K and one or more alkali metal elements selected from Li, Na, Rb, and Cs. From the viewpoint of chemical stability, it is preferred that the content ratio of K in element A is high (for example, 50 mol% or more of element A is K), and it is more preferred that element A is a simple substance.

[0054] The element M is a simple substance of Si, a simple substance of Ge, or a combination of Si and one or more elements selected from Ge, Sn, Ti, Zr and Hf. From the viewpoint of chemical stability, it is preferred that the content ratio of Si in the element M is high (for example, more than 50 mol % of the element M is Si), and it is more preferred that the element M is a simple substance of Si.

[0055] (Ratio of phosphor particles having micro-concave portions in phosphor powder)

[0056] When phosphor particles are used in a composite or a light-emitting device described later, phosphor powder, which is an aggregate of phosphor particles, is generally used.

[0057] The ratio of phosphor particles having at least one micro-concave portion on the surface in the phosphor powder is, for example, 10% or more, preferably 30% or more, more preferably 50% or more, and further preferably 75% or more, based on the number of particles. This value can be obtained, for example, by confirming whether at least 50 phosphor particles in an electron microscope image have micro-concave portions.

[0058] The cumulative 50% value in the volume-based particle size distribution curve of the phosphor powder is defined as D 50 When D 50 It is preferably 10 μm to 40 μm, and more preferably 20 μm to 35 μm. 50 When the value is appropriate, sufficiently sufficient quantum efficiency can be easily obtained, or when it is necessary to mix phosphor powder with resin or the like to form a film or sheet containing the phosphor in LED packaging applications, a uniform and smooth film or sheet can be easily formed.

[0059] In addition, the cumulative 10% value in the volume-based particle size distribution curve of the phosphor powder is defined as D 10 , the cumulative 50% value is set to D50 , the cumulative 90% value is set to D 90 When (D 90 -D 10 ) / D 50 It is preferably 1.2 or less, more preferably 0.9 or less, and further preferably 0.75 or less. The lower limit is not particularly limited, and is, for example, 0.3 or more, and specifically 0.5 or more.

[0060] (D 90 -D 10 ) / D 50 It can be understood as an indicator of the "width" of the particle size distribution. A narrow width of the particle size distribution of the phosphor powder means that the particle sizes of the phosphor particles in the phosphor powder are relatively "uniform". 90 -D 10 ) / D 50 When the ratio is 0.9 or less, for example, when it is necessary to mix phosphor powder with resin or the like to form a film or sheet containing the phosphor, it is easy to form a uniform and smooth film or sheet. In addition, in the manufacture of LED packages, nozzle clogging can be suppressed.

[0061] The volume-based particle size distribution curve can be obtained by measuring using a laser diffraction scattering method. For details of the measuring method, please refer to the examples described below.

[0062] <Method for producing phosphor particles>

[0063] The phosphor particles of this embodiment can be manufactured by using appropriate materials, selecting appropriate manufacturing methods and manufacturing conditions. Below, the preferred manufacturing steps are described. It is speculated that by adopting the steps described below, it is possible to produce a local supersaturation level during crystal growth, so that the growth rate changes, resulting in the formation of micro-concave portions.

[0064] (1) Preparation of hydrofluoric acid

[0065] Hydrofluoric acid (HF aqueous solution) is placed in a corrosion-resistant container and kept ready for use. The concentration of hydrogen fluoride is preferably 50 to 60% by mass.

[0066] (2) Cooling of hydrofluoric acid and injection of KHF2

[0067] While cooling the hydrofluoric acid prepared in the above (1), KHF2 is added and stirred. Then, while continuing to stir, the beaker is cooled. The cooling is preferably carried out until the temperature in the beaker is -35°C to 0°C, more preferably -15°C to -2°C, and further preferably -10°C to -5°C. According to the present inventors' understanding, by cooling the beaker in this way and then carrying out the following steps (3) and thereafter, the growth pattern of the crystal is controlled, and phosphor particles with tiny recesses are easily obtained.

[0068] It should be noted that during the following steps (3) and thereafter, cooling may be continued or stopped to allow the mixture to gradually approach room temperature. Theoretically, the former is preferred because it is easier to control various matters, while the latter is advantageous in terms of production cost (energy saving).

[0069] (3) Adding a raw material containing Mn and a raw material containing Si at the same time

[0070] The raw material containing Mn and the raw material containing Si are simultaneously added to the beaker cooled in (2) and stirred. The detailed reason is not clear, but the "simultaneous addition" of the two raw materials may be related to the formation of micro-concave portions in the phosphor particles.

[0071] As raw materials containing Mn, hexafluoromanganate, permanganate, oxide (excluding permanganate), fluoride (excluding hexafluoromanganate), chloride, sulfate, nitrate can be cited. Among them, from the aspect of being able to efficiently replace Mn at the Si site in the fluoride phosphor to obtain good luminescence characteristics, fluoride is preferred, and among the fluorides, hexafluoromanganate is preferred. As hexafluoromanganate, Na2MnF6, K2MnF6, Rb2MnF6, etc. can be cited. In particular, K2MnF6 is preferred because it contains F and K (equivalent to element A) that constitute the fluoride phosphor in addition to Mn.

[0072] As a raw material containing Si, SiO 2 can be preferably mentioned. From the aspect of easy availability and easy acquisition of a high-purity substance, SiO 2 is preferred as a raw material containing Si.

[0073] (4) Feeding of raw materials containing Mn (preferably in multiple times)

[0074] After the two raw materials are added in the above (3) and stirred for 30 to 60 seconds, the raw material containing Mn is added to the beaker.

[0075] The raw material containing the necessary amount of Mn is preferably added in multiple times (preferably 2 to 5 times). It is believed that by doing so, the elemental composition is homogenized in the phosphor particles (to avoid Mn being concentrated in the center). This is preferred from the perspective of further improving the luminescent properties.

[0076] Specific examples of the raw material containing Mn are as described in the above (3).

[0077] The obtained phosphor particles are recovered by solid-liquid separation by filtration, etc., and washed with an organic solvent such as methanol, ethanol, acetone, etc. If the fluoride-based phosphor is washed with water, a part of it is hydrolyzed to generate a brown manganese compound, which sometimes reduces the characteristics of the phosphor. Therefore, it is preferred to use an organic solvent in the washing process.

[0078] In addition, before cleaning with an organic solvent, if the hydrofluoric acid reaction solution is used for repeated cleaning, the impurities generated in trace amounts can be dissolved and removed. From the viewpoint of suppressing the decomposition of the fluoride phosphor, the concentration of the hydrofluoric acid in the hydrofluoric acid reaction solution used for cleaning is preferably more than 5 mass %, and from the viewpoint of the solubility of the phosphor, it is preferably below 60 mass %. After the cleaning process, preferably the cleaning solution is fully evaporated by drying.

[0079] Alternatively, a sieve with a predetermined mesh size may be used for classification or to remove coarse particles.

[0080] <Complex, light-emitting device>

[0081] The composite body of this embodiment includes the above-mentioned phosphor particles and a sealing material that seals the phosphor particles.

[0082] Furthermore, the light-emitting device of this embodiment includes: a light-emitting element that emits excitation light, and the above-mentioned complex that converts the wavelength of the excitation light.

[0083] The light-emitting device of this embodiment can be preferably used as a backlight of a display, for example.

[0084] Below, refer to Figure 2 An example of the complex and the light-emitting device will be described.

[0085] Figure 2 is a schematic diagram of the light emitting device 1.

[0086] The light emitting device 1 includes a complex 10 and a light emitting element 20. The complex 10 is provided in contact with an upper portion of the light emitting element 20.

[0087] The light emitting element 20 is typically a blue LED. A terminal is present at the bottom of the light emitting element 20. The light emitting element 20 can emit light by connecting the terminal to a power source.

[0088] The excitation light emitted from the light emitting element 20 is wavelength-converted by the composite 10. When the excitation light is blue light, the blue light is wavelength-converted into red light by the composite 10 including the phosphor particles.

[0089] The composite 10 may be composed of the above-mentioned phosphor particles and a sealing material that seals the phosphor powder. The composite 10 may further include phosphor particles that do not correspond to the above-mentioned phosphor particles.

[0090] As the sealing material, for example, various curable resin materials (materials that cure by heat and / or light) can be used. Any curable resin material can be used as long as it is sufficiently transparent and can obtain the optical properties required for a display or lighting device.

[0091] As the sealing material, for example, a silicone resin material can be cited. As for the silicone resin material, from the viewpoint of high transparency and excellent heat resistance, a curable silicone resin material supplied by Dow Corning Toray Co., Ltd., Shin-Etsu Chemical Co., Ltd., etc. is also preferred. In addition, as the sealing material, an epoxy resin material, a polyurethane resin material, etc. can also be cited.

[0092] The amount of the phosphor particles (the above phosphor particles and phosphor particles not corresponding to the above phosphor particles) in the composite 10 is, for example, 10 to 70 mass %, or preferably 25 to 55 mass %.

[0093] The size and shape of the light emitting element 20 are not particularly limited. The light emitting element 20 may be of any size and shape depending on the application of the light emitting device 1 .

[0094] For the sake of caution, Figure 2 The light emitting device 1 shown is a so-called chip-type light emitting device. The light emitting device to which the phosphor particles of this embodiment are applied is not limited to the chip-type, and may be a shell-type, a multi-segment type, or the like.

[0095] The embodiments of the present invention are described above, but these are examples of the present invention, and various configurations other than the above can be adopted. In addition, the present invention is not limited to the above embodiments, and modifications and improvements within the scope of achieving the purpose of the present invention are included in the present invention.

[0096] Example

[0097] Embodiments of the present invention will be described in detail based on Examples and Comparative Examples. However, for the sake of caution, it is to be noted that the present invention is not limited to Examples.

[0098] <Raw materials>

[0099] As raw materials, the following were used.

[0100] HF: 55% by mass aqueous solution manufactured by STELLA CHEMIFA CO., LTD.

[0101] K2SiF6: Made by Morita Chemical Co., Ltd.

[0102] K2MnF6: A substance prepared by the method described in paragraph 0042 of Japanese Patent Application Publication No. 2019-001897

[0103] KHF2: Special grade reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0104] SiO2: FB-50R manufactured by DENKA Co., Ltd.

[0105] <Manufacturing of phosphor particles>

[0106] (Example 1)

[0107] The phosphor particles are produced through the following steps.

[0108] (1) 2100 mL of a 55 mass % HF aqueous solution was placed in a Teflon (registered trademark) beaker at room temperature.

[0109] (2) While cooling the HF aqueous solution, add 315 g of KHF2 and stir. Continue to cool the beaker while stirring until the temperature in the beaker reaches -7°C.

[0110] (3) Add 4 g of K2MnF6 and 72 g of SiO2 into a beaker at -7°C and stir for 45 seconds.

[0111] (4) While continuing to cool to -7°C, 4 g of K2MnF6 was added to the beaker and stirred for 45 seconds.

[0112] (5) While continuing to cool to -7°C, 4 g of K2MnF6 was further added to the beaker and stirred for 45 seconds.

[0113] (6) While continuing cooling to -7°C, 4 g of K2MnF6 was further added to the beaker and stirred for 25 minutes.

[0114] After stirring, the solution was allowed to stand to precipitate the yellow solid component. After confirming the precipitation, the supernatant was removed, and the yellow solid component was washed with hydrofluoric acid having a concentration of about 24% by mass, and then washed with methanol. The washed solid component was filtered to separate and recover the solid component, and the residual methanol was further evaporated by drying. After drying, a nylon sieve with a mesh size of 75 μm was used, and only the yellow powder passing through the sieve was classified and recovered.

[0115] Through the above operation, phosphor particles are obtained.

[0116] (Example 2)

[0117] Phosphor particles were obtained in the same manner as in Example 1 except that cooling was stopped between the above steps (2) and (3), that is, the temperature in the beaker was allowed to naturally approach room temperature gradually after the above step (3).

[0118] Figure 3 , an electron microscope image of the phosphor particles obtained in Example 1 is shown. Figure 4 2 shows an electron microscope image of the phosphor particles obtained in Example 2.

[0119] As shown in the electron microscope images, phosphor particles having minute recessed portions on the surface were obtained in Examples 1 and 2.

[0120] According to the electron microscope images, most of the micro-recesses have triangular openings. The maximum diameter of the openings confirmed by the electron microscope images (when the opening is triangular, it is the length of the longest side of the triangle) falls within the range of about 1 μm to 20 μm. Specifically, Figure 3 The maximum diameter of the triangular opening of the particle surrounded by the circle is about 5 μm. Figure 4 The maximum diameter of the triangular opening of the particle surrounded by the circle is about 9 μm.

[0121] In addition, from each electron microscope image, secondary particles formed by aggregation of primary particles were confirmed, and micro recessed portions were also confirmed on the surface of the secondary particles.

[0122] In addition, the major diameter of the phosphor particles having micro-concave portions on the surface in each microscope image falls within the range of approximately 10 μm to 100 μm.

[0123] (Comparative Example 1)

[0124] With reference to the description of Patent Document 2 (International Publication No. 2009 / 119486), phosphor particles were obtained according to the following steps. The following steps were performed at room temperature.

[0125] (1) First, 100 mL of HF aqueous solution (46-48%), 6 g of KMnO4 and 100 mL of H2O were mixed to obtain a solution.

[0126] (2) 0.38 g of a 0.635 mm thick silicon wafer cut from an n-type dummy wafer was placed in the above solution and allowed to stand for 48 hours.

[0127] (3) After the solution was left to stand, the supernatant was removed and the remaining solid (precipitated crystals and dissolved silicon wafers) was washed with methanol. Then, the dissolved silicon wafers were manually removed.

[0128] Through the above operation, phosphor powder is obtained.

[0129] Figure 5 The electron microscope image of the obtained phosphor particles is shown in FIG. Figure 3 , Figure 4 Such a tiny recess having an opening.

[0130] <Identification: Crystal phase measurement, composition measurement, etc.>

[0131] The phosphor powder (yellow powder) obtained in each example was subjected to an X-ray diffraction apparatus to obtain an X-ray diffraction pattern. The obtained X-ray diffraction pattern was the same pattern as that of K2SiF6 crystal. This confirmed that K2SiF6:Mn was obtained in a single phase.

[0132] <Particle size distribution measurement by laser diffraction scattering method>

[0133] 30 mL of ethanol was measured in a 50 mL beaker, and 0.03 g of phosphor powder was added thereto. Next, the container was placed in a homogenizer (manufactured by Nippon Seiki Seisaku-sho, trade name US-150E) whose output was adjusted to "Altitude: 100%" in advance, and pre-treated for 3 minutes.

[0134] The solution prepared in this manner was used as the object, and a laser diffraction scattering particle size distribution measuring device (manufactured by Microtrac Bell, trade name MT3300EXII) was used to obtain a volume-based particle size distribution curve. Then, D was calculated from the obtained curve. 10 , D 50 and D 90 .

[0135] [Table 1]

[0136] Table 1

[0137] <![CDATA[D 10 ]]> <![CDATA[D 50 ]]> <![CDATA[D 90 ]]> <![CDATA[(D 90 -D 10 ) / D 50 ]]> Example 1 21.0 31.2 45.9 0.80 Example 2 20.4 30.6 45.3 0.81

[0138] <Evaluation of light-emitting characteristics (quantum efficiency, etc.)>

[0139] In the integrating sphere Side opening A standard reflector with a reflectivity of 99% (manufactured by Labsphere, trade name Spectralon) was set. The monochromatic light with a wavelength of 455 nm from the light source (Xe lamp) was introduced into the integrating sphere through an optical fiber, and the spectrum of the reflected light was measured using a spectrophotometer (manufactured by Otsuka Electronics, trade name MCPD-7000). At this time, the number of excitation light photons (Qex) was calculated based on the spectrum in the wavelength range of 450 to 465 nm.

[0140] Next, the phosphor powder obtained in each embodiment is filled in a concave groove in a smooth surface manner and then placed in the opening of an integrating sphere. Monochromatic light with a wavelength of 455nm is irradiated, and the spectra of the excited reflected light and fluorescence are measured using a spectrophotometer. The number of excited reflected light photons (Qref) and the number of fluorescent photons (Qem) are calculated based on the obtained spectral data. The number of excited reflected light photons is calculated within the same wavelength range as the number of excitation light photons, and the number of fluorescent photons is calculated within the range of 465 to 800nm. The absorption rate (= (Qex-Qref) / Qex×100), internal quantum efficiency (= Qem / (Qex-Qref)×100) and external quantum efficiency (= Qem / Qex×100) are calculated from the three photon numbers obtained.

[0141] The above results are summarized in Table 2.

[0142] [Table 2]

[0143] Table 2

[0144] Absorption(455nm) Internal quantum efficiency External quantum efficiency Example 1 82% 86% 70% Example 2 81% 88% 71% Comparative Example 1 71% 60% 43%

[0145] As shown in the above table, the light emitting properties of the phosphor particles of Examples 1 and 2 are good.

[0146] This application claims the benefit of priority based on Japanese patent application No. 2021-052759, filed on March 26, 2021, and all the contents disclosed therein are incorporated herein by reference.

Claims

1. A phosphor particle, the composition of which is represented by the following general formula (1): The surface has at least one micro-concave portion with a maximum diameter of 1 μm to 10 μm. The micro-concave portions exist on the surface of the substantially planar phosphor particles. General formula (1): A2MF6:Mn In the general formula (1), Element A is K alone, or a combination of K and one or more alkali metal elements selected from Li, Na, Rb, and Cs, The element M is Si as a single substance, Ge as a single substance, or a combination of Si and one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf.

2. The phosphor particle according to claim 1, wherein The opening of the micro recess has a triangular shape.

3. The phosphor particle according to claim 1 or 2, wherein The phosphor particles are secondary particles formed by aggregation of primary particles. 4 . A composite comprising: the phosphor particles according to claim 1 , and a sealing material that seals the phosphor particles. 5 . A light-emitting device comprising: a light-emitting element that emits excitation light, and the composite according to claim 4 that converts the wavelength of the excitation light.

Citation Information

Patent Citations

  • Fluoride phosphor and light-emitting device using the same

    JP2019001897A

  • Heating smokable material

    JP2021052759A

  • Fluorescent material, process for producing the same, and white-light-emitting diode employing the fluorescent material

    WO2009119486A1